Management of The Academic Potential of Students During The Covid-19 Pandemic - M. Rafiquddin Nasution; Mesiono Mesiono; Yusuf Hadijaya (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2021)
This article aims to analyze the management of fostering the academic potential of students during the Covid-19 pandemic at MTsN Tanjungbalai City. The focus of the discussion includes management functions (planning, implementation, supervision, supporting, and inhibiting factors in the process of fostering student potential. This study uses a qualitative approach with a descriptive method. The results of this study indicate that (1) planning is carried out at the beginning of each semester, including the determination of the learning system online or offline, fostering activities for students to take part in online madrasa science competitions (KSMO) and implementing home visits; (2) the implementation of learning is considered good, this is indicated by the presence of active teachers and education staff (the evidence is finger print results), students learning from via the WhatsApp Group application, coaching students to take part in KSMO, conducting home visits by teachers for students who have no news during the application of online learning; (3) supervision is carried out directly by the head of madrasa and deputy head of madrasa (WKM) in the academic field using mobile phone facilities and madrasa internet network h connected to all online groups of students and teachers; and (4) supporting factors, namely the activeness of teachers in providing guidance to students, while the inhibiting factors are the students' economy which is inadequate to access the internet network, many students who are not actively studying online in class groups, and the discovery of students who quit school during the Covid-19 pandemic.